ANALISIS TINGKAT KEPUASAN PELANGGAN MOBILE PAYMENT - Prihatiningsih Prihatiningsih; Ida Savitri Kusmargiani; Nina Woelan Soebroto (Politeknik Negeri Semarang, 2020)
Electronic money is a payment system that has been adopted and developed in the banking world. An example of electronic money is e-Toll Card, BCA Flazz, GazCard, BNI TapCash, BRI BRIZZI, BTN Blink and others. The use of electronic money as an innovative and practical means of payment is expected to help smooth payments for mass, fast and micro economic activities, so that their development can help smooth transactions on toll roads, in the field of transportation such as trains or other public transportation or transactions in mini. market, food court or parking. The problem in this study is the gap between smartphone users and mobile payment users, complaints from mobile payment users, and differences in the results of previous studies. The purpose of this study is to analyze the significance of the effect content, accuracy, format, timeliness and easy of use either simultaneously or partially on customer satisfaction mobile payment formulate and user satisfaction mobile paymentlevels. The population in this study wereusers mobile payment using purposive sampling technique, the sample in this study was the Semarang State Polytechnic Student who used the Dana.OVO, dan Go Pay application. using theanalysis method Satisfactio End User Computing.